Spatial Distribution and Ecological Risk of Microplastic Contamination in River Water Near a Landfill Leachate Disposal Area: A Case Study of Supit Urang Landfill, Malang City, Indonesia - Bahrudin, Moh. Zainal; Prayogo, Tri Budi; Haribowo, Riyanto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Microplastics (MPs) in landfill leachate are a critical environmental challenge due to their persistence in natural environment, where they resist degradation and pose long-term environmental risks, including harm to aquatic ecosystems and human health. Specifically, Supit Urang Landfill in Malang discharges leachate containing microplastics into the Sumber Beling River, which flows through the densely populated areas of Mulyorejo and Bandulan. This poses a significant risk, as public awareness of microplastic pollution remains low, and residents continue using the river for activities like fishing, washing, and bathing. This study examines the distribution and properties of microplastics in Sumber Beling River and assessed their ecological risk levels. Nine sampling points were chosen to represent pollution sources, upstream quality controls, and downstream sites impacted by pollution. We employed ATR-FTIR spectroscopy for its high accuracy in identifying microplastics, along with an ecological risk assessment using PHI, PLI, and PERI. The results revealed that microplastic abundance varied between 63 and 240 particles / L, with the highest concentration found in densely populated areas (TS.7). The predominant shapes of MPs were films (48.30%) and fragments (42.98%), with polypropylene (PP) and polyethylene (PE) being the most prevalent polymers detected. Although the overall ecological risk was low, site P5, located in the densely populated residential area of Mulyorejo, exhibited a high risk level. These findings underscore the urgent need for targeted interventions in densely populated areas to enhance waste disposal and raise community awareness regarding microplastic pollution.